Russian in the 1740s - Rosén, Thomas (Academic Studies Press, 2020)
Accounts of the development of the Russian language during the eighteenth century concentrate on the formation of a new literary language, and on the language of a few male authors. But what about the linguistic situation outside the elites? Why do general handbooks have so little to say about the language of ordinary people? Why is there such a focus on the language of imaginative literature when, for most of the century, there were so few original works? These are some of the questions raised in this investigation of Russian in the 1740s.